The Influence of Learning Video Media on the Learning Outcomes of Class VIII Students in Social Sciences Subjects at SMPN 39 Padang - Rizka, Miftahul; Kurnia yusri, Meldi Ade; Zuwirna, Zuwirna; Anugrah, Septryan (Lembaga Penelitian dan Pendidikan Mandala, 2023)
AbstractThis research aims to evaluate the effect of using video learning media on the learning outcomes of class VIII students in Social Sciences (IPS) subjects at SMP Negeri 39 Padang. This type of research is experimental research. With samples from classes VIII/4 and VIII/5 which consist of 2 classes, namely the experimental class and the control class. The experimental class, namely class VIII/5, was treated using learning videos and the control class, namely class VIII/4, was treated using textbooks. The sample used was Purposive Sampling. This research was conducted on social studies subjects with material on Indonesia's Resource Potential. By processing data using Normality Test, Homogeneity Test and Hypothesis Test. To test the hypothesis, this research uses the t test statistic, with a significance level of α 0.05. The research results showed that the average score for the experimental class that used learning video media was 76.40. The average score for the control class that used the textbook was 71.80. Based on the calculation of the t test (t-test), tcount is 2.52, whereas ttable is at a significant level of α 0.05 = 2.02. When compared, so tcount > ttable is 2.52 > 2.01. Which means that H1 is accepted. Thus, the use of learning video media has a significant effect on the learning outcomes of Class VIII students in Social Sciences Subjects at SMP N 39 Padang.